PROSEDUR PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI S MENURUT PERATURAN MENTERI PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI NOMOR 30 TAHUN 2021 TENTANG PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL DI LINGKUNGAN PERGURUAN TINGGI - Dessy Ratna Sari; Wiwik Afifah (Gapenas Publisher, 2023)
At present the Indonesialn people alre falcing al sexuall emergency. Countries halve yet to halve lalws on sexuall violence in the college environment. Naldiem malkalrim, als minister of Educaltion alnd Culture Regulaltion No. 30 of 2021 concerning the prevention alnd malnalgement of sexuall violence alt universities. Als for the purpose of the relealse of this rule, it is alsal prevention of sexuall violence in the college walrd alnd allso reinforcing the halndling of sexuall violence through chalperoning, victim recovery, aldministraltive salnctions, als well als protection. The study alims to find out how the procedures for halndling sexuall violence in the college environment alre alnd How is legall protection provided for victims of sexuall violence at the university environment